Tivozanib for the treatment of renal cell carcinoma: patient selection and perspectives - Rodenburg RJ; Eskens FALM (International Journal of Nephrology and Renovascular Disease, 2019)
RJ Rodenburg, FALM EskensErasmus MC Cancer Institute, Department of Medical Oncology, Rotterdam, The NetherlandsAbstract: Tivozanib is an oral selective vascular endothelial growth factors receptor (VEGFR) tyrosine kinase inhibitor that is recently approved by the European Medicines Agency for the treatment of previously untreated patients with metastatic renal cell carcinoma (mRCC) as well as for those patients with disease progression during or after cytokine therapy. Nowadays, in first-line and second-line treatment of mRCC, there is an abundance of options, mainly consisting of VEGFR-directed tyrosinekinase inhibitors. This review focusses on the role of tivozanib with respect to patient selection and future perspectives in this fast-changing landscape.Keywords: tivozanib, metastatic renal cell cancer, tyrosine kinase inhibitor